2015
DOI: 10.15537/smj.2015.7.11463
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of thyroid cancer in patients with hyperthyroidism

Abstract: Objectives:To determine the prevalence of thyroid cancer in patients with hyperthyroidism.Methods:This is a retrospective observational study using the data of 71 Omani patients with a diagnosis of hyperthyroidism due to Grave’s disease, toxic multinodular goiter, and solitary toxic adenoma. These patients underwent thyroidectomy at the Royal Hospital (RH), Muscat, Oman, and were followed up at the National Diabetes and Endocrine Center (NDEC) between 2007 and 2013. The details were collected from the medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
(20 reference statements)
2
7
0
Order By: Relevance
“…Clinical hypothyroidism seems to be a risk factor for several neoplasias such as liver cancer, thyroid malignancies, high-grade glioblastomas and human breast cancer (Reddi et al 2007, Polyzos et al 2008, Hassan et al 2009, Angelousi et al 2012. In contrast, increased TH levels have been associated with higher risk of esophageal, thyroid, breast and ovarian cancer development (Turkyilmaz et al 2005, Rasool et al 2014, Kunjumohamed et al 2015. Changes in the intracellular TH concentration due to alterations in the deiodinases status seem to be critical for modulating cell proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical hypothyroidism seems to be a risk factor for several neoplasias such as liver cancer, thyroid malignancies, high-grade glioblastomas and human breast cancer (Reddi et al 2007, Polyzos et al 2008, Hassan et al 2009, Angelousi et al 2012. In contrast, increased TH levels have been associated with higher risk of esophageal, thyroid, breast and ovarian cancer development (Turkyilmaz et al 2005, Rasool et al 2014, Kunjumohamed et al 2015. Changes in the intracellular TH concentration due to alterations in the deiodinases status seem to be critical for modulating cell proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The majority (73–84.5%) of subjects were female. Seven studies 28 , 30 , 31 , 33 , 34 , 36 , 37 had available data on thyroid microcarcinoma, which contributed to 65.59% of the total cancer occurrence. The definitions of GD and hyperthyroidism were based on clinical decisions and symptoms (diagnostic details are shown in Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…All definitions of thyroid cancer were based on postsurgical pathological results (histological definitions and classifications can be seen in Table S2 ). Besides GD, four studies 27 , 28 , 34 , 36 included surgery-treated hyperthyroid patients with TA, while ten studies 28 37 included those with TNG. The indications as well as types of thyroidectomy are also listed in Table S1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional studies performed in Saudi Arabia have shown that the primary tumor size is 2.3 cm (23 mm), and the other tumor size is 2.15 cm (21.5 mm) [ 2 ]. Earlier studies showed that females were affected more often than males; the cause behind the females' higher incidence is not well understood [ 2 , 22 ]. However, in this study, both genders were equal.…”
Section: Discussionmentioning
confidence: 99%